Analysis of the Spatial-Temporal Evolution of Ecological Footprint of Water Resources in Yunnan Province - HAN Lihong; PAN Yujun; MA Jiashen; YANG Dongqi; YANG Xiaolin; LIU Hua (Renmin Zhujiang)
The ecological footprint of water resources is a hot topic of current water resources research.Based on the water resources ecological footprint model,this paper analyzes the temporal and spatial evolution of water resources in Yunnan Province from 2008 to 2018,and then discusses the dynamic development of water resources in the province.The results show that:①From 2008 to 2018,the province's water resources ecological footprint showed a “W”-shaped fluctuating trajectory.The value of agricultural water ecological footprint is the highest among the four types of water resources ecological footprint,indicating that the consumption of water resources by agricultural development is the largest.The carrying capacity,ecological surplus and ecological pressure index of water resources are all in a sustainable development state;the ecological footprint of water resources per 10 000 yuan of GDP is decreasing year by year,and the water consumption efficiency is continuously improving.②In 2008,2013 and 2018,the spatial development of ecological footprint of water resources per capita was unbalanced,and the ecological surplus of water resources per capita was basically in shortage;the ecological footprint of water resources per 10 000 yuan of GDP showed a downward trend,indicating that the industry structure of all cities and prefectures is continuously upgraded,and the water consumption efficiency is continuously improved.